Posterior reversible encephalopathy syndrome following iatrogenic acetylcysteine overdose: a case report - James Jae; Yilong Li; Constance A. Mackenzie (Toxicology Communications, 2023)
AbstractWe present a case of posterior reversible encephalopathy syndrome (PRES) linked to N-acetylcysteine (NAC) overdose during treatment for acetaminophen overdose. The patient presented to the emergency department following the ingestion of 455 mg/kg of acetaminophen and was administered a total of 46.2 g of NAC over 14 h in error, compared to the intended 19.8 g. She subsequently developed status epilepticus. After seizure control, brain imaging by CT and MRI showed PRES. Continuous renal replacement therapy (CRRT) was started to eliminate NAC and acetaminophen. The patient eventually recovered neurologically with improved transaminases and was free of further seizures.